PERLINDUNGAN HUKUM TERHADAP PEJABAT PEMBUAT AKTA TANAH (PPAT) PENERIMA PROTOKOL (Studi Kasus Putusan Nomor 83/Pdt.G/2011/PN.SKA) - , GHUSNIE ARINI A ([Yogyakarta] : Universitas Gadjah Mada, 2014)
The study aims to learn about law protection to Official Certifier of Title Deeds as protocol receiver in case study decision No. 83/Pdt.G/2011/PN.SKA. and to determine the role of Ikatan Pejabat Pembuat Akta Tanah (IPPAT) to provides protection for Official Certifier of Title Deeds as protocol receiver. This study is an empirical normative research using primary and secondary data through library research and field research. The results showed that in the judge's decision did not provide legal protection for PPAT protocol receiver. Organizationally, IPPAT already provide protection for its members through the section of the field butis passive. Based on the results, we conclude PPAT protocol should be submitted to the BPN/local Land Office. Less than the maximum IPPAT organizations in providing protection to its members because it is passive. Keywords : Law Protection, Official Certifier of Title Deeds, Official Certifier of Title Deeds Protocol